Blended learning and working options in the aftermath of the COVID-19 pandemic. Issue 3 (14th February 2022) - Oyelude, Adetoun A.
Abstract : Purpose: Because blended working options have emerged and varied technological devices are being used during lockdowns, it is necessary to examine the working and learning options in the aftermath of the COVID-19 pandemic. The pros and cons of hybrid (blended) working and learning are highlighted. Design/methodology/approach: An extended search of literature online, and also of examples of blended learning and working instituted in some libraries, archives and museums was carried out over a period of three weeks. Findings: Findings indicated that adjustments to the hybrid working and learning situations had to be made by staff and students in heritage institutions. Provision of more digital content and the adoption of machine learning models were the solutions proffered, with indications that the tools for the blended learning implementation be provided. Reskilling of staff due to new technologies being introduced is recommended. Originality/value: Solutions to blended learning and blended working scenarios are provided, giving pointers to online links for added information.